Rhamnolipid Nano-Micelles versus Alcohol-Based Hand Sanitizer: A Comparative Study for Antibacterial Activity against Hospital-Acquired Infections and Toxicity Concerns - Yasmin Abo-zeid; Marwa Reda Bakkar; Gehad E. Elkhouly; Nermeen R. Raya; Dalia Zaafar (MDPI AG, 2022)
Hospital-acquired infections (HAIs) are considered to be a major global healthcare challenge, in large part because of the development of microbial resistance to currently approved antimicrobial drugs. HAIs are frequently preventable through infection prevention and control measures, with hand hygiene as a key activity. Improving hand hygiene was reported to reduce the transmission of healthcare-associated pathogens and HAIs. Alcohol-based hand sanitizers are commonly used due to their rapid action and broad spectrum of microbicidal activity, offering protection against bacteria and viruses. However, their frequent administration has been reported to be associated with many side effects, such as skin sensitivity, skin drying, and cracks, which promote further skin infections. Thus, there is an essential need to find alternative approaches to hand sanitation. Rhamnolipids are glycolipids produced by Pseudomonas aeruginosa, and were shown to have broad antimicrobial activity as biosurfactants. We have previously demonstrated the antimicrobial activity of rhamnolipid nano-micelles against selected drug-resistant Gram-negative (Salmonella Montevideo and Salmonella Typhimurium) and Gram-positive bacteria (Staphylococcus aureus, Streptococcus pneumoniae). To the best of our knowledge, the antimicrobial activity of rhamnolipid nano-micelles in comparison to alcohol-based hand sanitizers against microorganisms commonly causing HAIs in Egypt-such as Acinetobacter baumannii and Staphylococcus aureus-has not yet been studied. In the present work, a comparative study of the antibacterial activity of rhamnolipid nano-micelles versus alcohol-based hand sanitizers was performed, and their safety profiles were also assessed. It was demonstrated that rhamnolipid nano-micelles had a comparable antibacterial activity to alcohol-based hand sanitizer, with a better safety profile, i.e., rhamnolipid nano-micelles are unlikely to cause any harmful effects on the skin. Thus, rhamnolipid nano-micelles could be recommended to replace alcohol-based hand sanitizers; however, they must still be tested by healthcare workers in healthcare settings to ascertain their antimicrobial activity and safety.